On Modern Methods And Means Of Protection In Computer Networks - A.T. Utepbergenova (Periodica Journal, 2025)
This article discusses modern methods and tools for protecting information in computer networks. Technical, software, cryptographic and organizational measures used to ensure information security are covered in detail. Also, unauthorized access methods, methods for their prevention, the importance and practical application of cryptographic protection mechanisms are analyzed. The article provides a detailed classification of information protection tools - formal, informal, technical, software, organizational, ethical and legal aspects.
Keywords: Information security; computer networks; protection methods